Ánalise do efeito comportamental no índice bovespa: um estudo interdisciplinar - Ramos, Andre Luiz (2007)
The theory and identification of stock market behavioral reactions should be perceived as a contribution to a better understanding of this financing instrument - the Stock Market. This piece of work aims to study, analyze, and perceive the financial market in order to contribute for a better understanding of reactions not clearly explained by the traditional financial theory. It is an attempt to incorporate some behavior theories in a way to add to the explanations about some market movements not only the economical, financial, or political variables, but also information on how human beings react as investors in several situations they are exposed to. After this theoretical work, it was carried out a study trying to prove the existence of financial market anomalies in Brazilian market. I was used some statistical approach of BOVESPA Index, based on a number of data accrued from BOVESPA price closure daily indexes. Such information was obtained at the Broadcast database and covers the period from March 1997 to July 2005. The statistical analysis of market inefficiency was not able to prove the existence of price barriers once prices didn t reflect the true value around the psychological levels of reference. Therefore, this study could not infer in the existence of irrationality according to its parameters. However, it didn t infer in the inexistence of this proposition either, because in current market globalization, indexes are not analyzed in the light of the same conversion unit, and this might be the reason why statistics research has not been successful